(untitled) (Journal of Humanitarian and Applied Sciences, 2017)
Abstract The results of concentration of Ni in the three sites was within the limits allowed by the WHO , and noticed that the soil samples Does not contain Chrome in the three studied sites while Pb concentration are higher in soil more depth and exceeded the limits allowed. The presence of sources of pollution in the area of libda- the city of Alkoms Libya that prodced from the steam plant for desalination of water, waste water, waste of cars, chemical waste, generators and some small factories, exposure of beaches to pollution and therefore, affect human health, this research was done to measure the pollution of some heavy metals in certain area of the coastal area of lebeda- alkoms, The study area was divieded into three sites and samples were taken with equal distances and three different depths for each region. These samples were analyzed to measure the concentration of Ni,Cr,Pb, elements.. The concentration of heavy metals in the surface soil was less than the concentration in the other depths of all the samples , and the concentration of the metals in first site (at the wave) was less than in the third site ( far from the wave).